Liver-Specific Expression of Constitutively Active G(s)α Leads to Hyperglycemia With Impaired Insulin Secretion - Sun, Hui (J Endocr Soc, 2021)
Liver-specific Expression of Constitutively Active G(s)α Leads to Hyperglycemia With Impaired Insulin Secretion The ubiquitously-expressed G protein G(s)α couples hormone receptors to the stimulation of intracellular cAMP generation. We previously showed that mice with liver-specific G(s)α deficiency (LGsKO) have improved glucose tolerance and enlarged pancreatic islets(1). In the present study, we have generated mice with liver-specific expression of a constitutively activated G(s)α (LGsR201C) by breeding mice containing a Lox-STOP-Lox-G(s)αR201C transgene within the Hipp11 locus with albumin-Cre mice. Male LGsR201C mice had normal survival but reduced body weight and increased liver weight. Compared to control littermates, LGsR201C mice had significantly increased hepatic cAMP levels and enhanced hyperglycemic response to glucagon, confirming the activation of liver G(s)α/cAMP signaling in LGsR201C mice. As a consequence, LGsR201C mice showed elevated blood glucose levels during both fed and fasting states, as well as enhanced hepatic gluconeogenesis evidenced by pyruvate tolerance test. Serum levels of insulin, glucagon, free fatty acids and triglycerides were comparable between control and LGsR201C mice in the fed state. Results of glucose and insulin tolerance tests showed that LGsR201C mice had severe glucose intolerance with normal insulin sensitivity. Unlike control mice, when given a high dose of glucose (3mg/g ip.), LGsR201C mice had completely blunted first- and second-phase insulin secretory responses to glucose. Since LGsR201C mice exhibited normal pancreatic islet size and insulin content examined with immunohistochemistry, the impaired glucose tolerance in LGsR201C mice probably resulted from an impaired insulin secretion. Results of RNA-seq analysis revealed that an array of genes was oppositely regulated in the liver of LGsKO mice vs. LGsR201C mice. Thus, our data indicate possible organ-to-organ communication between liver and pancreatic β-cells that is regulated by liver G(s)α signaling. 1.Chen M., et al., JCI 115:3217, 2005